Experimental study of different oxides in B2O3–ZnO–BaO glass system for gamma-ray shielding - Mohamed Elsafi; M. I. Sayyed; Taha A. Hanafy (Scientific Reports)
Abstract Glass system of 45B2O3–20ZnO–30BaO–5X, (where X represents CaO, MgO, Al2O3, TiO2, CuO and Fe2O3) in mole percentage was investigated for gamma ray radiation shielding experimentally. Six glass composites were fabricated and the density was measured experimentally and the BZBCa glass sample has the least density with a value of 3.932 g cm−3 and this is due to the presence of CaO in it, and the sample BZBFe has the highest density with a value of 4.031 g cm−3. Through comparing the linear attenuation coefficient (LAC) data (experimental and Phy-X) for the BZBX glass samples, the LAC values for glass samples obtained experimentally and using Phy-X are in a very close range. All the glass samples have the greatest LAC values at 0.0595 MeV, the lowest energy value. Sample BZBCu has a LAC value of 16.203 1/cm, which is also the highest LAC value among all the studied glasses, this is as a result of the high density of this glass and due to the high atomic number of Cu. The glasses’ transmission factor (TF) at 1 cm thickness against energy was determined. The TF values of all the glasses were almost zero. The TF values increased significantly for all the glasses when the energy was increased to 0.662 MeV, and for sample BZBCa its TF value increases 74.08%, which was the highest TF value increase. The half-value layer and other shielding parameters have been determined experimentally.